2002
DOI: 10.1007/s00107-002-0293-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of air emissions from industrial kiln drying of Pinus radiata wood

Abstract: The nature and mass flows of atmospheric emissions from an industrial kiln, drying radiata pine (Pinus radiata D. Don) at 100°C dry bulb and 70°C wet bulb, were assessed by measuring the concentration of chemical components in the kiln atmosphere at regular time intervals and determining air-flows and temperature differentials across the stack. The volatile organic compounds (VOC) were trapped on activated carbon and analyzed by GC-MS. The aldehydes were trapped in 2,4-dinitrophenol-hydrazine solution and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…Examples of typical thermal degr adation products are methanol, formaldehyde (Barry and Corneau, 2006;Su et al, 1999), acetaldehyde (McDonald et al, 1995), pentanal, hexanal (Otwell et al, 2000) formic acid, acetic acid, alcohols and furfurals (Bridgwater et al, 1995). There are studies published on thermic degradation emissons from lumber drying (McDonald et al, 2002;Milota, 2006), rotary drum drying of fragmented wood (Banerjee et al, 2006) and drying in a ceramic tube furnace (Otwell et al, 2000;Su et al, 1999). The results from these studies are not necessarily transferable to the drying of sawdust in spouted/fluidized beds.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of typical thermal degr adation products are methanol, formaldehyde (Barry and Corneau, 2006;Su et al, 1999), acetaldehyde (McDonald et al, 1995), pentanal, hexanal (Otwell et al, 2000) formic acid, acetic acid, alcohols and furfurals (Bridgwater et al, 1995). There are studies published on thermic degradation emissons from lumber drying (McDonald et al, 2002;Milota, 2006), rotary drum drying of fragmented wood (Banerjee et al, 2006) and drying in a ceramic tube furnace (Otwell et al, 2000;Su et al, 1999). The results from these studies are not necessarily transferable to the drying of sawdust in spouted/fluidized beds.…”
Section: Introductionmentioning
confidence: 99%
“…McDonald et al (2002) reported that in addition to the monoterpene emissions, small amounts of diterpenes were present. In the present work a large amount of pimaral is released when drying the heartwood of pine at higher temperatures (above 708C).…”
Section: Concentration Of Analytes and Emission Rates From Heartwood mentioning
confidence: 97%
“…The appropriateness (Word et al 1998) as well as the inappropriateness (McDonald et al 2002) of this method for detection of compounds such as formaldehyde, formic acid and methanol have been emphasized. An alternative method has been reported by Dallons et al (1994) who utilized a Total Hydrocarbon Analyzer to measure the levels of VOC from wood samples obtained before and after the drying process.…”
Section: Introductionmentioning
confidence: 99%
“…편백나무는 열기 건조가 진행 되는 동안 다양한 휘발성 유기화합물들을 포함한 기체를 발생한 다 (Cronn et al, 1983;Mcdonald and Wastney, 1995). 지금까지 편백나무의 정유성분에 대한 생리활성 효과로는 항생효과, 살충 효과, 타감효과 등이 보고되고 있다 (Yaeno et al, 2003;Gwak et al, 2006;Park et al, 2008 (Englund and Nussbaum, 2000;McDonald et al, 2002). 이와 같은 terpenoids는 식물 자신의 보호 기능을 넘어 인 간에게 항 염, 항 바이러스, 항 박테리아, 면역기능 강화 등의 효 과를 가지고 있다 (Soliman et al, 1994;McGarvey and Croteau, 1995;Vila et al, 1999).…”
Section: 편백나무(Chamaecyparis Obtuse)는 상록침엽교목으로 일본 이 원산지이며 1904년에 도입되어 unclassified